1996
DOI: 10.1021/ja9609157
|View full text |Cite
|
Sign up to set email alerts
|

Blackbody Infrared Radiative Dissociation of Bradykinin and Its Analogues:  Energetics, Dynamics, and Evidence for Salt-Bridge Structures in the Gas Phase

Abstract: Blackbody infrared radiative dissociation (BIRD) spectra of singly and doubly protonated bradykinin and its analogues are measured in a Fourier-transform mass spectrometer. Rate constants for dissociation are measured as a function of temperature with reaction delays up to 600 s. From these data, Arrhenius activation parameters in the zero-pressure limit are obtained. The activation parameters and dissociation products for the singly protonated ions are highly sensitive to small changes in ion structure. The A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

36
427
4
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 385 publications
(471 citation statements)
references
References 79 publications
36
427
4
1
Order By: Relevance
“…Presumably, these ion pairs can be formed simultaneously by the same mechanism if, when the amide bond cleaves, one ionizing proton is located on each of the newly formed b n and y m−n ions. Williams and co-workers have shown by blackbody infrared dissociation (BIRD) that the lowest energy fragmentation pathway for doublyprotonated bradykinin results in the formation of the b 2 /y 7 ion pair [29]. This is supported by molecular dynamics simulations which demonstrate the protonated N-terminal arginine is partially solvated by the backbone carbonyl oxygen of the proline residue in the second position, which likely contributes to formation of the b 2 and y 7 ions [29].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Presumably, these ion pairs can be formed simultaneously by the same mechanism if, when the amide bond cleaves, one ionizing proton is located on each of the newly formed b n and y m−n ions. Williams and co-workers have shown by blackbody infrared dissociation (BIRD) that the lowest energy fragmentation pathway for doublyprotonated bradykinin results in the formation of the b 2 /y 7 ion pair [29]. This is supported by molecular dynamics simulations which demonstrate the protonated N-terminal arginine is partially solvated by the backbone carbonyl oxygen of the proline residue in the second position, which likely contributes to formation of the b 2 and y 7 ions [29].…”
Section: Introductionmentioning
confidence: 91%
“…Later studies by Guevremont and co-workers using high-field asymmetric waveform ion mobility spectrometry (FAIMS) combined with H/D exchange detected four separate bradykinin populations, including one of very low abundance, for the doubly-protonated peptide [23]. In general, ion mobility and H/D exchange results support a compact, folded conformation for both singly-and doublyprotonated bradykinin in which the basic and acidic sites interact [10,16,29]. The existence of a salt-bridge, in which the carboxy terminus is deprotonated and both arginine residues are protonated, has been proposed for singly-and doubly-protonated bradykinin [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…However, an understanding of the relationship between gas phase structure and solution conformation is still at a very primitive stage, in large part because detailed gas phase structural information is limited. In addition to chemical probes of gas phase ion structure [1][2][3][4][5][6][7][8][9][10][11][12][13][14], a number physical methods are being developed to examine gas-phase peptide and protein ion structure [15][16][17][18][19][20][21][22][23][24][25][26][27], including collisional activation to examine fragmentation pathways [18 -23, 25-27]. A few studies have suggested that ion conformation may influence fragmentation pathways [19,23,27,28].…”
mentioning
confidence: 99%
“…A number of different methods can provide information about molecular structure in the gas phase, even complex systems, such as large synthetic or biological polymers. These methods include spectroscopy [1][2][3][4][5], hydrogen/deuterium exchange [6-12], dissociation [13][14][15][16][17][18], proton transfer reactivity [19][20][21][22], and ion mobility mass spectrometry . These methods have been used to obtain information about protein conformation and folding, DNA duplex structure, and in a wide variety of other interesting applications.…”
mentioning
confidence: 99%
“…Zwitterions are destabilized in the gas phase compared with solution, but there is considerable evidence that these ionic interactions play a key role in the structure and reactivity of biomolecules in the gas phase [13,14,60,61]. Bowers and coworkers have used ion mobility mass spectrometry to examine the structure of cationized amino acids and related molecules.…”
mentioning
confidence: 99%